PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN TEKNIK MENERAN “TIUP” TERHADAP BIDAN, KADER DAN IBU HAMIL DI WILAYAH KARAWANG BARAT KABUPATEN KARAWANG - Rahayu Pertiwi; Ida Farida Handayani; A.Achmad Fariji; Imam Makhrus (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
One of the factors causing perineal tears is the way of pressing in the second stage of labor. Several studies have shown that the “Blow” breathing technique at the end of the second stage of labor is an effective method of reducing excessive pressure on the perineum. But in general, most women do the pressing technique with the Valsalva technique, which is a strong and long pressing technique that has the risk of large perineal tears and fetal asphyxia. The results of the author's survey in the Karawang district obtained data from 20 postpartum mothers, 17 of whom experienced a perineal tear during childbirth, and they said they were still using the traditional menan technique (Valsava). This community empowerment activity is to improve the knowledge and skills of midwives, cadres and pregnant women regarding the "blowing" technique. The activity is carried out through training in the "Blow" technique by providing theory and demonstration of the pushing technique in the second stage of labor. The activity was carried out for seven face-to-face meetings, starting from August to October 2020. The targets of the activity were midwives, cadres, and pregnant women in the second and third trimesters in the Tanjungpura sub-district, Karawang district. There was an increase in the knowledge value of midwives from an average of 6.5 (pre-test) to 9 (post-test), and from an average of 4.05 (pre-test) to cadres and pregnant women to 7.16 (post-test), all training participants were able to demonstrate the pushing technique during labor properly and correctly. The delivery of menan technique training can increase the knowledge and skills of menan technique in midwives, cadres and pregnant women, so that it is expected to reduce the rate of perineal tears and fetal asphyxia.